The relationship between deliberate practice, play, and futsal in childhood and adolescence and the development of different decision-making skills in professional female soccer players - Machado, G.; González-Víllora, S.; Teoldo, I. (Psychology of Sport and Exercise, 2023)
Soccer players` ability to make efficient and quick decisions has gained more importance due to the increase in game speed in the last few years. Therefore, this study aimed to examine the relationship between the engagement in previous developmental activities in soccer and futsal with the quality and speed of decision-making skills in different phases of sport development of elite female soccer players. The sample comprised 77 elite Brazilian professional female soccer players. Players` decision-making skills were assessed based on an objective video-based test - TacticUP®. We used a retrospective questionnaire to collect information about previous participation in different developmental activities. The results showed that engagement in deliberate practice in soccer and futsal, especially during childhood and early adolescence, is related to a better quality of offensive decision-making skills, although showing small to medium effect sizes. We highlight that deliberate practice in futsal is associated only with offensive decision-making skills with the ball and near the ball. In turn, engaging in deliberate play in soccer, mainly in childhood and early adolescence, is related to quicker offensive and defensive decision-making skills, showing mostly medium effect sizes. To the best of our knowledge, it was the first study to measure the relationship of decision-making speed with developmental activities in soccer. It is concluded that deliberate practice in soccer and deliberate play in soccer are associated with different dimensions of decision-making skills.